Assessing Students’ Listening Skills Through Pictures - Suyik Binakarbeni; Adriadi Novawan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2004)
The integration of English into local content curricula in Indonesian elementary schools has created an urgent need for effective assessment methods tailored to young learners. Recognizing that children’s cognitive and perceptual worlds differ from adults’, this study addresses the gap in understanding how picture-based media can facilitate listening comprehension assessment. The research aimed to describe the listening abilities of fifth-grade pupils at SDN Jember Lor III, focusing on their capacity to understand English words, phrases, and expressions through pictures. A descriptive quantitative design was employed, involving 50 pupils who took a listening test using picture-based items. Data were analyzed using descriptive statistics. The findings revealed that the mean listening score was 79.9, categorized as good, with listening for main ideas (mean 87.6, very good) outperforming listening for detailed information (mean 74.9, more than enough). The study concludes that pictures are effective media for assessing and teaching English listening to primary school pupils and recommends intensified practice in listening for detailed information through activities such as transcription tasks and Simon Says games. Memasukkan bahasa Inggris ke dalam kurikulum muatan lokal di sekolah dasar Indonesia menciptakan kebutuhan mendesak akan metode asesmen yang efektif bagi pelajar anak. Menyadari bahwa dunia kognitif dan persepsi anak berbeda dengan orang dewasa, penelitian ini bertujuan mendeskripsikan kemampuan menyimak siswa kelas V SDN Jember Lor III melalui media gambar, khususnya pemahaman mereka terhadap kata, frasa, dan ungkapan bahasa Inggris. Penelitian deskriptif kuantitatif ini melibatkan 50 siswa yang diberikan tes menyimak berbasis gambar. Data dianalisis secara statistik deskriptif. Hasil penelitian menunjukkan bahwa nilai rata-rata kemampuan menyimak siswa adalah 79,9 (kategori baik), dengan kemampuan menyimak ide pokok (rata-rata 87,6, sangat baik) lebih tinggi daripada kemampuan menyimak informasi rinci (rata-rata 74,9, lebih dari cukup). Penelitian ini menyimpulkan bahwa gambar adalah media yang efektif untuk asesmen dan pembelajaran menyimak bahasa Inggris di sekolah dasar. Direkomendasikan agar latihan menyimak informasi rinci ditingkatkan melalui aktivitas seperti tugas transkripsi dan permainan Simon Says.